Cognitive based interventions for elderly people with mild cognitive impairement: Review of effects and efficacy - Fátima González Palau; Manuel Franco Martin; Fernando Jiménez; Mara Bernate; Esther Parra; José Miguel Toribio; Abdel Solis; Raquel Losada; Teresa Cid (CAEN, 2012)
Due to the significant increase in the percentage of older adults, as well as degenerative diseases, there is growing interest in the determination of effective psychosocial approaches aimed to subjects with mild cognitive impairment (MCI). Recent experimental studies indicate positive effects of cognitive interventions in population with DCL in both, traditional methods and computer based interventions. The present review provides a systematic analysis of the literature in order to assess the effect and scope of actual non-pharmacological cognitive interventions, aimed to older adults with mild cognitive impairment.